Luhmanns massmedieteori och Internet som ett artificiellt intelligent semiotiskt system [Luhmann’s mass-media theory and Internet as an artificial intelligent semiotic system] - Kåhre, Peter (MedieKultur: Journal of media and communication research, 2010)
The article discusses how a modern form of AI programming, known as Connectionism in a design known as Distributed Artificial Intelligence (DAI), affects the perception Luhmann has on mass media’s role concerning second-order observations. DAI uses nodes to create activity in the systems and not the codes used by the Classic or Symbolic form of AI. Luhmann’s theory can be developed by replacing the systems codes with nodes that change depending on their relations to other nodes. In this way, we can reformulate the concept of communication, so that it includes the systems interactions with the environment. It creates better conditions so that observing opportunities may arise directly from these interactions. Internet and AI-programmed search systems and robots can then act as an artificial semiotic system that creates opportunities for making observations.